Clutch parasitism and nesting interference between Shelducks at Aberlady Bay - Pienkowski, M W; Evans, P R (Wildfowl, 1982)
Intra-specific nesting interference in Shelducks Tadorna tadorna was studied, using nest-boxes, at Aberlady Bay, SE Scotland, where the ducks normally nest in rabbit burrows. The mean size of non-parasitized clutches was 8.9 eggs and the mean incubation period 32 days. At least one-third of clutches investigated were laid by more than one female. These had a significantly higher chance of desertion than clutches laid by one duck. Large numbers of eggs in one clutch also led to exclusion of some, and to a reduction in the incubation temperature (and delayed development) of those remaining. The possible reasons for clutch-parasitism are discussed.